Persulfide Dioxygenase From Acidithiobacillus caldus: Variable Roles of Cysteine Residues and Hydrogen Bond Networks of the Active Site - Rühl, Patrick; Haas, Patrick; Seipel, Dominik; Becker, Jan; Kletzin, Arnulf (Frontiers in Microbiology, 2018)
Persulfide dioxygenases (PDO) are abundant in Bacteria and also crucial for H2S detoxification in mitochondria. One of the two pdo-genes of the acidophilic bacterium Acidithiobacillus caldus was expressed in Escherichia coli. The protein (AcPDO) had 0.77±0.1 Fe/subunit and an average specific sulfite formation activity of 111.5 U/mg protein (Vmax) at 40 ˚C and pH 7.5 with sulfur and GSH following a Michaelis-Menten kinetic. KM for GSH and Kcat were 0.5 mM and 181 s-1, respectively. Glutathione persulfide (GSSH) as substrate gave a sigmoidal curve with a Vmax of 122.3 U/mg protein, a Kcat of 198 s-1 and a Hill coefficient of 2.3±0.22 suggesting positive cooperativity. Gel permeation chromatography and non-denaturing gels showed mostly tetramers. The temperature optimum was 40-45 ˚C, the melting point 63±1.3 ˚C in thermal unfolding experiments, whereas low activity was measurable up to 95 ˚C. Site-directed mutagenesis showed that residues located in the predicted GSH/GSSH binding site and in the central hydrogen bond networks including the iron ligands are essential for activity. Among these, the R139A, D141A and H171A variants were inactive concomitant to a decrease of their melting points by 3-8 K. Other variants were inactivated without significant melting point change. Two out of five cysteines are likewise essential, both of which lie presumably in close proximity at the surface of the protein (C87 and C224). MalPEG labeling experiments suggests that they form a disulfide bridge. The reducing agent Tris(2-carboxyethyl)phosphine was inhibitory besides N-ethylmaleimide and iodoacetamide suggesting an involvement of cysteines and the disulfide in catalysis and/or protein stabilization. Mass spectrometry revealed modification of C87, C137 and C224 by 305 mass units equivalent to GSH after incubation with GSSH and with GSH in case of the C87A and C224A variants. The results of this study suggest that disulfide formation between the two essential surface-exposed cysteines and Cys-S-glutathionylation serve as a protective mechanism against uncontrolled thiol oxidation and the associated loss of enzyme activity.